Switching to PegIFNα-2b leads to HBsAg loss in patients with low HBsAg levels and HBV DNA suppressed by NAs. Issue 1 (December 2017) - Huang, Jing; Zhang, Ka; Chen, Wenli; Liao, Jinyao; Luo, Xiaodan; Chen, Ren
Abstract Patients with low hepatitis B surface antigen (HBsAg) levels and hepatitis B virus (HBV) DNA suppression by nucleos(t)ide analogues (NAs) achieve high rate of HBsAg loss through switching to PegIFNα in pre-registration study. The aim of this study was to achieve higher rate of HBsAg loss through extended PegIFN treatment. 98 patients with HBsAg < 2, 000 IU/ml and HBV DNA < 20 IU/ml were randomized to receive PegIFNα-2b or continuing NA therapy for 60 weeks. At the end of treatment (EOT) and end of follow-up (EOF), only patients who switched to PegIFNα-2b achieved HBsAg loss (32.6%) and HBsAg seroconversion (27.9% and 25.6%). Patients who switched to PegIFNα-2b also achieved higher HBeAg seroconversion rates (65.1%) and HBeAg loss (81.4% and 90.7%) than those who continued NAs treatment. On-treatment HBsAg declines predicted the responses at EOT, and HBsAg declines at post-baseline times predicted the responses at EOF. The rates of responses were not increased through extended PegIFNα treatment. For patients with low HBsAg and HBV suppression with NAs, switching to PegIFNα-2b significantly increased the rates of HBsAg loss and HBsAg seroconversion. HBsAg decline can predict the response of switching to PegIFNα-2b following from NAs.